2013
DOI: 10.1016/j.ijhydene.2013.01.185
|View full text |Cite
|
Sign up to set email alerts
|

High-pressure torsion of TiFe intermetallics for activation of hydrogen storage at room temperature with heterogeneous nanostructure

Abstract: TiFe is a potential candidate for the stationary hydrogen storage systems, but it requires initial activation to absorb hydrogen. This study shows that TiFe processed by highpressure torsion (HPT) absorbs and desorbs 1.7 wt.% hydrogen at room temperature without activation. The absorption pressure decreases from 2 MPa in the first hydrogenation cycle to 0.7 MPa in the latter cycles. The HPT-processed TiFe exhibits heterogeneous microstructures composed of nanograins, coarse-grains, amorphous-like phases and di… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
53
0
2

Year Published

2015
2015
2024
2024

Publication Types

Select...
8
1

Relationship

3
6

Authors

Journals

citations
Cited by 133 publications
(55 citation statements)
references
References 47 publications
0
53
0
2
Order By: Relevance
“…This problem can be eliminated when TiFe is preprocessed by HPT (Fig. 8) 97 or by other SPD techniques because hydrogen diffusion is facilitated through the introduction of a high density of microcracks and grain boundaries. Furthermore, the HPT-processed sample is not deactivated even after storage in air.…”
Section: Spd-processed Hydrogen Storage Materialsmentioning
confidence: 99%
“…This problem can be eliminated when TiFe is preprocessed by HPT (Fig. 8) 97 or by other SPD techniques because hydrogen diffusion is facilitated through the introduction of a high density of microcracks and grain boundaries. Furthermore, the HPT-processed sample is not deactivated even after storage in air.…”
Section: Spd-processed Hydrogen Storage Materialsmentioning
confidence: 99%
“…[112][113][114][115][116][117][118][119][120] Recent studies have shown that SPD processing is the way to achieve that, as such an activation process is no longer required when the TiFe is pre-processed by HPT ( Figure 15). [121] Furthermore, the HPT-processed sample is not deactivated even after storage in air for a prolonged period of time. [122] The mechanism enabling hydride formation without activation is associated with enhanced diffusion of hydrogen that occurs via HPTinduced microcracks and nanograin boundaries.…”
Section: Mg and Mgmentioning
confidence: 99%
“…[4][5][6][7][8][9][10] It is well known that the grain refinement to the submicrometer and/or nanometer range is achieved using the process of severe plastic deformation (SPD). [11] Although several processes are available for the SPD, [12,13] the process under high pressure, known as high-pressure torsion (HPT), [14][15][16] is effective for the grain refinement in hard and less ductile materials even such as intermetallics, [17][18][19][20][21][22] semiconductors, [23][24][25][26] and ceramics. [27,28] The sample for the HPT processing is used in a form of disk [14] or ring [29][30][31] and it may be extended to ribbons or wires if they are processed in a continuous way using continuous HPT (CHPT).…”
mentioning
confidence: 99%